Legacies of colonial English : studies in transported dialects - Hickey, Raymond, 1954- (Studies in English language., 2004)
As a result of colonisation, many varieties of English now exist around the world. Legacies of Colonial English explores the role of British dialects in both the genesis and subsequent history of postcolonial Englishes, and how it came about that many still reflect non-standard British usage from the distant past.